Outcome-focused Management and Budgeting - Kromann Kristensen, Jens (OECD Publishing, 2002)
Over the last two decades, the focus of public sector budgeting and management in most OECD Member countries has changed from inputs towards outputs. While important elements of an input-based management approach remain, many managers are now more often judged by how their programmes perform rather than by how well they adhere to administrative controls and procedures, or how successful they are in obtaining resources for their programme. The jury is still out as to the details of actual gains and losses connected to this change, but generally it is the view of central budgeting and management institutions that this change in focus has enhanced the quality of management and increased programme effectiveness and efficiency